1997
DOI: 10.1016/s0092-8674(00)80431-6
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of ClpP at 2.3 Å Resolution Suggests a Model for ATP-Dependent Proteolysis

Abstract: We have determined the crystal structure of the proteolytic component of the caseinolytic Clp protease (ClpP) from E. coli at 2.3 A resolution using an ab initio phasing procedure that exploits the internal 14-fold symmetry of the oligomer. The structure of a ClpP monomer has a distinct fold that defines a fifth structural family of serine proteases but a conserved catalytic apparatus. The active protease resembles a hollow, solid-walled cylinder composed of two 7-fold symmetric rings stacked back-to-back. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
581
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 568 publications
(605 citation statements)
references
References 57 publications
20
581
0
4
Order By: Relevance
“…The active site was then analyzed since the catalytic triad (Ser97-His122-Asp171) in ClpP is located in the cleft between the head domain and handle region (Wang et al, 1997). Previously, we reported that the catalytic triads in extended and ADEP-bound activated BsClpP showed very similar conformations, ruling out an allosteric activation mechanism (Lee et al, 2010a).…”
Section: Differences Between Compressed and Extended Formsmentioning
confidence: 99%
See 3 more Smart Citations
“…The active site was then analyzed since the catalytic triad (Ser97-His122-Asp171) in ClpP is located in the cleft between the head domain and handle region (Wang et al, 1997). Previously, we reported that the catalytic triads in extended and ADEP-bound activated BsClpP showed very similar conformations, ruling out an allosteric activation mechanism (Lee et al, 2010a).…”
Section: Differences Between Compressed and Extended Formsmentioning
confidence: 99%
“…In addition to the axial pore, we investigated the active site of ClpP. Previously, several ClpP structures representing inhibited or substrate-bound states have been reported (Kim and Kim, 2008;Szyk and Maurizi, 2006;Wang et al, 1997). The overall shape of all of these structures shows an extended conformation as in the case of DFPinhibited BsClpP, although the active sites and N-terminal segments of the apo and inhibited structures vary depending on the bacterial species.…”
Section: Conformational Diversity Of Clppmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] ClpP is a multisubunit serine peptidase, in which the proteolytic active sites reside within a barrel-shaped structure. 5 ClpX is a hexameric AAAþ enzyme (ATPases associated with a variety of cellular activities), which recognizes substrates and uses cycles of ATP-powered conformational changes to unfold the native protein and to translocate the denatured polypeptide into the proteolytic chamber of ClpP for degradation. [6][7][8] ClpX typically identifies substrates by binding to degrons located near the protein termini.…”
Section: Introductionmentioning
confidence: 99%